Pedampingan Mahasiswa Thammasat University Thailand dalam Meningkatkan Keterampilan Berbahasa Indonesia dengan Pelatihan Membatik Khas Surakarta - Ani Rakhmawati; Kundharu Saddhono; Raheni Suhita; Sri Hastuti; Maulana Danar Maaliki H; Aldi Dwi Saputra; Muhammad Aditya Wisnu Wardana; Hamam Supriyadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to investigate the effectiveness of mentoring for Thammasat University Thailand students in improving Indonesian language skills through Surakarta batik training. Mentoring is considered an effective method in helping students acquire better language skills. This study involved a group of Thammasat University students who were studying Indonesian at the beginner level. They were given the opportunity to take part in Surakarta's typical batik training which involves practicing speaking, writing, and listening in Indonesian. The research method used is a qualitative approach with data collection techniques through observation, interviews, and document analysis. The collected data was analyzed using the content analysis method. The results of the study show that mentoring through typical Surakarta batik training is effective in improving the Indonesian language skills of Thammasat University students. Students reported significant improvements in their ability to speak, write, and understand Indonesian after participating in the training. This research makes an important contribution to our understanding of the importance of mentoring in improving foreign language skills, especially for international students. Surakarta's typical batik training has proven to have significant potential in facilitating Indonesian language learning, because it involves interactive and interesting cultural aspects.